NmrB (AN9181) expression is activated under oxidative stress conditions acting as a metabolic repressor of Aspergillus nidulans - Jorge, João M. P.; Martins, Celso; Domingos, Patrícia; Martins, Tiago M.; Hartmann, Diego O.; Goldman, Gustavo H.; Silva Pereira, Cristina (Frontiers in Microbiology, 2024)
Aspergilli comprise a diversity of species that have been extensively studied due to their catabolic diversity, biotechnological and ecological value, and pathogenicity. An impressive level of structural and functional conservation has been shown for aspergilli, regardless of many (yet) cryptic genomic elements. We have hypothesized the existence of conserved genes responsive to stress in aspergilli. To test the hypothesis of such conserved stress regulators in aspergilli, a straightforward computational strategy integrating well-established bioinformatic tools was used as the starting point. Specifically, five transcriptome-based datasets on exposure to organic compounds were used, covering three distinct Aspergillus species. Among the identified up-regulated genes, only one gene showed the same response in all conditions, AN9181. This gene encodes a protein containing a phenylcoumaran benzylic ether reductase-like domain and a Nitrogen metabolite repressor regulator domain (NmrA). Deletion of this gene caused significant phenotypic alterations compared to that of the parental strain across diverse conditions. Specifically, the deletion of AN9181 raised the mutant's metabolic activity in different nitrogen sources. The acquired data supports that AN9181 acts by repressing (slowing down) A. nidulans growth when exposed to aromatic compounds in a concentration dependent manner. The same phenotype was observed for amphotericin B. Finally, AN9181 underwent differential upregulation under oxidative stress conditions. Collectively, the data suggest that AN9181, herein assigned as NmrB (Nitrogen Metabolite Repression Regulator B), builds up the genetic machinery of perception of oxidative stress by negatively regulating growth under such conditions.